تقصي انتشار الإصابة بالكيسة العدارية و الكيسة المذنبة دقيقة الرقبة في المجترات الصغيرة المذبوحة في مسلخ مدينة اللاذقية - نيصافي, علي; نعمة, فؤاد; جبلاوي, غنوة (Latakia University Journal -Biological Sciences Series, 2019)
لتقصي انتشار الإصابة بالكيسة العدارية (المائية) والكيسة المذنبة دقيقة الرقبة في المجترات الصغيرة المذبوحة في مسلخ مدينة اللاذقية , تم فحص (3300) ذبيحة :( 2450 غنم ,850 ماعز) . بلغت نسبة الإصابة بالكيسات العدارية فيها على التوالي : 6,16% , 11,52% , و كانت نسبة الكيسات المخصبة عند هذه الحيوانات كما يلي: %25 في الأغنام و%31,25 في الماعز مما يشير إلى الدور الوبائي الهام الذي تلعبه الماعز ثم الأغنام في نشر الإصابة بداء الكيسات العدارية. كانت الكيسات كلها وحيدة البؤرة و توضعت عند الأغنام في الكبد بنسبة 59,60% و56,12%في الماعز و في الرئة بنسبة 23,17%عند الأغنام و 30,61% عند الماعز و في كل من الكبد و الرئة بنسبة 17,21% في الأغنام و 13,26% في الماعز. أما بالنسبة للكيسة المذنبة دقيقة الرقبة فقد توضعت الإصابة في الثرب و المساريقا و بلغت نسبتها في الأغنام و الماعز على التوالي 23,67% و 36,47%. وقد بينت الدراسة أن نسبة الإصابة بالكيسة العدارية و الكيسة المذنبة دقيقة الرقبة تزداد مع تقدم عمر الحيوان , وخلصت إلى جملة من المقترحات الخاصة بمنع انتشارها و الوقاية منها . To investigate the infection with Hydatid Cyst and Cysticercus Tenuicollis in small Ruminants slaughtered in Abattoir of Lattakia – City – Syria, a total of (3300) slaughtered food animals. (2450 ) sheep and ( 850) goats were examined. Results of investigation showed that ( 6.16%) of sheep and (11,52%) of goats were infected with hydatid cysts. The percentage of the fertile hydatid cysts was as follow:( 25%) in sheep and (31.25%) in goats. It means that goats and sheep play a major role in epidemic prevalence of infection with Hydatid cyst. All hydatid cysts were unicolor ones, and they were found in the inner organs and in the bowels as following : in the sheep: in liver (59,60%) , in lungs (23,17%) and together in liver and lungs (17,21%) . in the goats : in liver (56,12%) in lungs (30,61%) and together in liver and lungs (13,26%).The cysticercus tenuicollis was found in Omentum and Mesenterium and infection rate was (23.67%) in the sheep and (36.47%) in the goats . The study showed that the rate of infection increased due to the age of animal, and concluded a series of recommendations to prevent spreading and control of these parasitic diseases.